Rapamycin Protection of Livers From Ischemia and Reperfusion Injury Is Dependent on Both Autophagy Induction and Mammalian Target of Rapamycin Complex 2-Akt Activation. Issue 1 (January 2015) - Zhu, Jianjun; Lu, Tianfei; Yue, Shi; Shen, Xiuda; Gao, Feng; Busuttil, Ronald W.; Kupiec-Weglinski, Jerzy W.; Xia, Qiang; Zhai, Yuan
Abstract : Background: Although rapamycin (RPM) have been studied extensively in ischemia models, its functional mechanisms remains to be defined. Methods: We determined how RPM impacted the pathogenesis of ischemia-reperfusion injury (IRI) in a murine liver partial warm ischemia model, with emphasis on its regulation of hepatocyte death. Results: Rapamycin protected livers from IRI in the presence of fully developed liver inflammatory immune response. Rapamycin enhanced liver autophagy induction at the reperfusion stage. Dual mammalian (mechanistic) target of rapamycin (mTOR)1/2 inhibitor Torin 1, despite its ability to induced autophagy, failed to protect livers from IRI. The treatment with RPM, but not Torin 1, resulted in the enhanced activation of the mTORC2-Akt signaling pathway activation in livers after reperfusion. Inactivation of Akt by Triciribine abolished the liver protective effect of RPM. The differential cytoprotective effect of RPM and Torin 1 was confirmed in vitro in hepatocyte cultures. Rapamycin, but not Trin 1, protected hepatocytes from stress and tumor necrosis factor-α induced cell death; and inhibition of autophagy by chloroquine or Akt by Triciribine abolished RPM-mediated cytoprotection. Conclusion: Rapamycin protected livers from IRI by both autophagy and mTORC2-Akt activation mechanisms. Abstract : Rapamycin is shown to have a dual role in protecting murine livers from experimental ischemia reperfusion injury.